2018
DOI: 10.1042/bsr20180532
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormally expressed JunB transactivated by IL-6/STAT3 signaling promotes uveal melanoma aggressiveness via epithelial–mesenchymal transition

Abstract: Uveal melanoma (UM) is the most common primary intraocular tumor in adults, and it carries a high risk of metastasis and mortality. Various proinflammatory cytokines have been found to be significantly increased in the aqueous humor or vitreous fluid of UM patients; however, the role of these cytokines in UM metastasis remains elusive. In the present study, we found that long-term interleukin (IL)-6 exposure promoted the migration and invasion of UM cells, diminished cell–cell adhesion, and enhanced focal adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…Although STAT1 is known to be involved in mediating the anti-tumor immunity and other STAT families are known to be involved in the promotion of cancer development, it is STAT3 that is most well studied as a significant intrinsic transcription factor in the induction of the EMT and in the pathogenesis of cancer ( Figure 2) [16]. IL-6/JAK2/STAT3 activation enhances metastasis via induction of EMT by the upregulation of EMT-inducing transcription factors (EMT-TFs; Snail, Zeb1, JUNB, and Twist-1) and increases cell motility via focal adhesion kinase (FAK) activation [17][18][19][20]. In prostate cancer, paracrine IL-6/JAK2/STAT3 stimulates the autocrine IL-6 loop, and IGF-IR activation induced by both IL-6 and IGF enhances EMT through induction of the STAT3/NANOG/Slug axis [21,22].…”
Section: Role Of Il-6/jak/stat3 In the Induction Of Emtmentioning
confidence: 99%
“…Although STAT1 is known to be involved in mediating the anti-tumor immunity and other STAT families are known to be involved in the promotion of cancer development, it is STAT3 that is most well studied as a significant intrinsic transcription factor in the induction of the EMT and in the pathogenesis of cancer ( Figure 2) [16]. IL-6/JAK2/STAT3 activation enhances metastasis via induction of EMT by the upregulation of EMT-inducing transcription factors (EMT-TFs; Snail, Zeb1, JUNB, and Twist-1) and increases cell motility via focal adhesion kinase (FAK) activation [17][18][19][20]. In prostate cancer, paracrine IL-6/JAK2/STAT3 stimulates the autocrine IL-6 loop, and IGF-IR activation induced by both IL-6 and IGF enhances EMT through induction of the STAT3/NANOG/Slug axis [21,22].…”
Section: Role Of Il-6/jak/stat3 In the Induction Of Emtmentioning
confidence: 99%
“…In addition, METTL3-provoked m 6 A methylation of ZMYM1 mRNA facilitated EMT and gastric cancer metastasis [ 19 ]. Some studies have demonstrated that EMT promotes the metastasis and aggression of UM [ 20 , 21 ]. However, the effect of m 6 A modifications on EMT in UM has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, functional assays aimed to investigate its implication in metastatic processes showed that LINC00518 expression increased not only after EMT-induction by IL6 and HGF treatment, but also after HIF1A activation by CoCl 2 treatment. It has been reported that IL6 and HGF trigger EMT in vitro [ 29 , 30 , 31 , 32 , 33 , 34 ], also in UM cells [ 35 , 36 ], while CoCl 2 provokes a hypoxia-like response through HIF1A activation [ 37 ], which represents one of the key events in the metastatic cascade [ 38 ]. Based on our results, IL6 seems to be more efficient in EMT induction in UM cells compared to HGF, as confirmed by the higher increase in EMT markers.…”
Section: Discussionmentioning
confidence: 99%